KETERBUKAAN INFORMASI DI PERADILAN DALAM RANGKA IMPLEMENTASI INTEGRITAS DAN KEPASTIAN HUKUM - Mansyur, Ridwan (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2015)
As a public institution in the field of justice, the Supreme Court is required to commit to apply the disclosure of information. Nowadays, transparency of information disclosure in the context of justice for the Supreme Court is not only the public needs but also the needs of all residents of the judiciary. With the judicial transparency, will slowly happen to strengthen accountability and professionalism and integrity of the judiciary residents. Commitment to provide disclosure of both the process and the end result is a concrete manifestation of public services as access to justice (access to justice) given by the Court at the lowest levels up to the Supreme Court.Â Quality of excellent public services through the transparency of the judicial information disclosure is the estuary of execution Reform of Bureaucracy.Keywords : Information transparency, Judicial, Integrity and Legal Certainty